APPLICATION OF ARTIFICIAL INTELLIGENCE IN INCREASING EMPLOYEE INTEGRITY - Imas komariyah (Jurnal Ekonomi, 2023)
Employee integrity is a key factor in creating a healthy and productive work culture. Artificial intelligence (AI) has the potential to support efforts to improve employee integrity through various applications, such as behavior monitoring, data analysis, and action recommendations. This research aims to explore the application of artificial intelligence in improving employee integrity in an organizational context. This research methodology includes literature analysis to understand the concepts of integrity, AI, and the relationship between the two using a qualitative approach and descriptive analysis. The research results show that the application of artificial intelligence (AI) in human resource management (HR) is able to help the employee recruitment process, increase the efficiency of employee training, analyze employee data, manage work schedules, and increase company productivity. The role of AI in improving employee integrity is in terms of monitoring behavior, data analysis, use of predictive algorithms, sentiment analysis, automatic reporting and action recommendations.